A Rare Presentation of Occipital Dermoid Cyst with Intracranial Extension and Secondary Infection: Case Report and Follow-Up - Li, Guyu; Kim, Jaechoon; Garcia, Matthew; Reyes-McChesney, Ivy; Hanna, Ashley; Bhalala, Utpal (Journal of Neurological Surgery Reports, 2024)
Craniofacial dermoid cysts are congenital anomalies that rarely have intracranial extension and can be associated with other anomalies. Common sites of these lesions are the lateral brow and parietal scalp. Presentation of the dermoid cyst in the occipital region with intracranial extension is extremely rare. We report a 2-year-old female with a presentation of an occipital dermoid cyst with intracranial extension and secondary cerebellar abscess. This case highlights the rarity of the presentation of an occipital dermoid cyst with intracranial extension and secondary infection and the importance of early imaging for suspected dermoid cysts in the occipital region for identification of intracranial extension.
Keywords: occipital dermoid cyst; pediatrics; intracranial abscess; case report